Investigating the Causes of Blindness and Vision Impairment in Children Younger Than 15 Years Old - Abbas Riazi; Fatemeh Riazi (Function and Disability Journal)
Background and Objectives: Vision impairment has very severe effects on education. It brings serious problems in life and job opportunities. In our country, Iran, accurate statistics on children with vision impairment and blindness are unavailable. Methods: This study examined only children up to 15 years old with vision impairment and blindness. Complete eye examinations were investigated, including vision measurement of both eyes for far and near, refraction to determine refractive errors, direct and indirect ophthalmoscopy, and checking the presence of any eye deviation. Standard LogMar charts were used. In addition, the need for visual aids was examined by a low-vision specialist. Results: A total of 708 blind and visually impaired children (371 boys and 337 girls) were examined. The average age of the participants was 3.50±8.99. Congenital retinal diseases include 42% of the causes of blindness and vision impairment in these children. Retinitis pigmentosa 9%, Leber congenital amaurosis (LCA) 8%, albinism <1%, refractive errors 9.5%, cortical visual impairment 13.6%, cataract and glaucoma each alone 7%, corneal opacity 1.7% and non-pathogenic causes, such as trauma <1% were diagnosed. A total of 63% of these children were the result of family marriage. Conclusion: The high percentage of family marriage among the parents of these children has also increased the probability of blindness and low vision. Many of these diseases are genetic; no specific treatment has yet been discovered. The lack of proper vision rehabilitation facilities in schools and access to vision aids make the residual vision not used in the critical age of the child. Therefore, the expansion of vision impairment rehabilitation services is a necessity.